Comparison of Cerb B2 expression and Ki-67 index with modified scarff-bloom-richardson grading system in invasive ductal carcinoma (Annals of Medical Research, 2021)
Aim: Breast cancer is the most frequent cancer among women. Cerb B2 is an oncogene that encodes a transmembrane glycoprotein known as HER-2 protein or receptor. Ki-67 is nuclear protein associated with cellular proliferation. In this study, we investigated the relationships between the histopathologic parameters in the “Modified Scarff-Bloom-Richardson” microscopic grading and expression of Cerb B2 and Ki-67 index gene in cases with invasive ductal carcinoma. Breast cancer is the most common type of cancer in women, but also the second most common cause of death after lung cancer.Material and Methods: In this study examined 45 patients who were diagnosed with invasive ductal carcinoma between January 2017 and January 2019 in Sivas Cumhuriyet University, department of surgical oncology. Cases, Cerb B2 expression and Ki-67 index were retrospectively screened from pathology recordsResults: Increased expression of Cerb B2 was statistically significant related with increased tubule formation, pleomorfism, mitosis rate, and histological grade (p=0.006, p=0.027, p0.001, p=0.001, respectively). Increased Ki-67 index was statistically significant related with increased tubule formation, pleomorphism, mitosis rate, and histological grade (p=0.031, p0.001, p=0.048, p=0.010, respectively).Conclusion: As a result, it was observed that there was a positive correlation between parameters included in Modified Scarff-Bloom-Richardson grading system with Cerb B2 expression and Ki-67 index. Cerb B2 and Ki-67 index are important prognostic biomarkers in human breast cancer.